Doctoral dissertations in nursing – research protocols in a multicenter comparative study - Teixeira-Santos, Luísa; Cerveny, Martin; Collins, Daniela; Nagórska, Małgorzata; Patel, Harshida; Shao, Joy; Sihvola, Saija; Simoes, Angela; Warshawski, Sigalit; Luiking, Marie-Louise (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Nursing doctoral research is vital for advancing the field, improving patient care, and addressing complex healthcare challenges. It contributes to evidence-based practices, innovative interventions, and the development of skilled nurse researchers and leaders, shaping the future of healthcare through enhanced knowledge and informed policy decisions. This scoping review aims to map the landscape of PhD dissertations in the nursing domain. Inclusion criteria: This scoping review will consider doctoral studies in nursing domain published in Dutch, English, Finnish, Hebrew, Portuguese, Polish, Slovak, Swedish, published between 2020–2023. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The search strategy was to find published literature in the following electronic databases: CINHAL, PubMed, SCOPUS, PsycINFO, Web of Science, Psychology & Behavioral Sciences Collection, and ERIC. Additionally, national repositories of several countries was explored, and contact established with universities represented by the members of this research team. The screening process entailed two steps carried out by two independent reviewers: firstly, screening by title and abstract and secondarily by full text. Data describes the literature according to the review research questions that were defined following the PPC mnemonic. Data will be presented graphically when possible and accompanied by a narrative that describes the Ph.D. dissertation characteristics. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Identifying areas of research in nursing contributes to the development of nursing as a science.